Application of rotifer Brachionus plicatilis in detecting the toxicity of harmful algae - 颜天 王云峰 王丽平 陈洋 韩刚 周名江 (Chinese journal of oceanology and limnology, 2009)
The toxicity of seven major HAB （harmful algal bloom） species/strains, Prorocentrum donghaiense, Phaeocystis globosa, Prorocentrum micans, Alexandrium tamarense （AT-6, non-PSP producer）, Alexandrium lusitanicum, Alexandrum tamarense （ATHK） and Heterosigma akashiwo were studied against rotifer Brachionus plicatilis under laboratory conditions. The results show that P donghaiense, P. globosa, P. micans, A. tamarense （AT-6）, or A. lusitanicum could maintain the individual survival and reproduction, as well as the population increase of the rotifer, but the individual reproduction would decrease when exposed to these five algae at higher densities for nine days; H. akashiwo could decrease the individual survival and reproduction, as well as population increase of the rotifer, which is similar to that of the starvation group, indicating that starvation might be its one lethal factor except for the algal toxins; A. tamarense （ATHK） has strong lethal effect on the rotifer with 48h LCs0 at 800 cells/mL. The experiment on ingestion ability indicated by gut pigment change shows that P. donghaiense, P. globosa, P micans, A. tamarense （AT-6） and A. lusitanicum can be taken by the rotifers as food, but A. tamarense （ATHK） or H. akashiwo can be ingested by the rotifers. The results indicate that all the indexes of individual survival and reproduction, population increase, gut pigment change of the rotifers are good and convenient to be used to reflect the toxicities of HAB species. Therefore, rotifer is suggested as one of the toxicity testing organisms in detecting the toxicity of harmful algae.